Adverse Drug Reactions: Predisposing Factors, Modern Classifications and Causality Assessment - Mainul, Haque; Nordin, Simbak; Abdullahi Rabiu, Abubakar (2014)
Several factors predispose patient to develop adverse drug reactions (ADRs), some of these factors are drug related, patient related, disease related, social and adverse drug related. The contributions of these factors to development of ADRs are very crucial and are well documented in medical literature. It has become necessary for every medical practitioner to consider these factors in order to prescribe the best medication to his patients. The current classification of ADRs is only based on drug known pharmacology and dose dependent of its action. In order to give comprehensive classification, the time course of its appearance and its severity as well as patient susceptibility are taken into consideration. Knowledge of causality assessment enables the medical practitioners to clarify the likelihood that the suspected adverse drug reaction is actually due to the medicine. This requires careful patient monitoring because adverse drug reaction can be difficult and a times impossible to distinguish from patient disease condition. The purpose of this article is to review the factors affecting the development of ADRs, its broader classification and to assess causal relationship between the suspected drug and appearance of ADRs.